The Value of Social Care Character Education through Zikir Tarekat Qadiriyah Wa Naqsyabandiyah - Suteja; M. Sugeng Sholehuddin; Irfan Hania (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aimed to find out and describe the pattern and model of character building for the students of the Qodiriyah wa Naqsyabandiyah Tarekat so that they have social care characters and the motives or reasons for students to follow the Qodiriyah wa Naqsyabandiyah Tarekat. This research is field research using a descriptive qualitative research approach. Data collection techniques in this study used observation, study, and the distribution of open questionnaires. The sample in this study found 38 people who are members of the Qodiriyah wa Naqsabandiyah Order. Finally, data analysis uses data reduction, presentation, and data retrieval by triangulation as a cross-check for the validity of the data. The results of this study indicate that the social care character education formed by the Qodiriyah wa Naqsabandiyah congregation uses two patterns, namely dhikr and tazkiyat al-Nafs. Developing the personality of Qodiriyahwa Naqsabandiyah Bongas Indramayu, as is usually the case in the tarekat world, is carried out using the dhikr method and soul adjustment (tazkiyat al-Nafs). Their motive for entering the tarekat is almost entirely based on economic motives. The coaching that has been carried out has not succeeded in creating the personality of students with social concerns in interacting with the community.